Role of DJ-1 in the Activation of AKT Via Binding and Inhibition of PHLDA3 Under Oxidative Stress - Don-Carolis, Katherine (Université d'Ottawa / University of Ottawa, 2015)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by the selective loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNc). PD affects ~1% of the population over 65, as demonstrated by characteristic symptoms such as tremor, rigidity, and bradykinesia. While the majority of PD cases are idiopathic, some cases are familial, including those caused by homozygous loss-of-function mutations in DJ-1 (PARK7), which lead to early onset PD. Although the physiological role of DJ-1 is not fully understood, DJ-1’s neuroprotective role against oxidative stress is well documented. DJ-1 is required for AKT-mediated neuroprotective effects, however the mechanism by which DJ-1 affects membrane localization/activation of AKT is unknown and is likely a critical aspect of DJ-1 function. In this thesis we explore the mechanism through which DJ-1 confers neuroprotection through AKT membrane recruitment, particularly in the case of oxidative stress insult. We demonstrate here that DJ-1 interacts with PHLDA3, a negative regulator of AKT, and loss of DJ-1 leads to hypersensitivity of neurons to PHLDA3-mediated death. Additionally, we demonstrate that in the absence of DJ-1, PHLDA3 localization at the membrane is increased, and overexpression of PHLDA3 causes reduced AKT phosphorylation in DJ-1 KO MEFs in response to oxidative stress. Taken together, these studies provide a potential novel mechanism by which DJ-1 regulates the activity of AKT, a critical neuronal survival pathway. Elucidation of these mechanisms may provide insight into the design of neuroprotective therapies for PD.
Keywords: Parkinson's Disease; DJ-1; AKT; PHLDA3